An Advanced Study on Strengthening Community Response; the Need for Enhanced Community Engagement. A Case for District Local Authorities in Developing Countries - Emmanuel Hakwia Kooma (Highlights on Medicine and Medical Science Vol. 7, 2021)
The study’s goals were to identify important elements impacting community participation and responsiveness in solid waste management in developing nations’ local governments. . Data base: explored using Cochrane libraries, CINAHL, and reports/policy papers. . WHO Journals and other research gave details on the processes (inform, consult, involve, collaborate and empower) including the guiding principles, content analysis of both unsuccessful and successful engagement of communities by the local authorities in developing countries. These theme topics were examined in light of the rising relevance of community and public engagement activities in local governments, which has resulted in a greater focus on skill development, engagement process monitoring, and assessment. The suggested conceptual framework was thoroughly researched, and a substantial literature evaluation was conducted. According to WHO guidelines, the proposed community engagement framework was deemed to be suitable for the present needs of local authorities in developing countries in public health practises. Content analysis of both unsuccessful and successful involvement in solid waste management by local governments in poor countries was used to study the construct in order to give the requisite guiding concepts, practices, and degrees of participation. Internal capacity restrictions, community capacity limits, other external variables, and other substantive hurdles were among the issues that these local governments encountered in community participation. Information transmission mechanisms, the engagement environment, community leaders/champions, external help, unconventional new ways, and the degree of involving indigenous people for effective community involvement were the six key themes that emerged from the study. A better understanding of community engagement procedures can give better results through long-term strategic planning, a high degree of effort to accommodate cultural differences, and the presence of an adequate and suitable information system to allow the local authority to efficiently capture, manage, and process relevant community engagement data such as community enquiries, requests, complaints,and also to provide timely feedback to the community.